[LB.02.32] ANTIHYPERTENSIVE DRUG TREATMENT FOR FIRST TRIMESTER HYPERTENSION GUIDED BY SERIAL AMBULATORY BLOOD PRESSURE MONITORING. (September 2017) - Gryglas, P.; Jedrusik, P.; Wojciechowska, E.; Gryglas, A.; Dabrowski, M.; Symonides, B.; Gaciong, Z.
Abstract : Objective: We used serial ambulatory blood pressure monitoring (ABPM) to guide antihypertensive drug treatment in pregnant women with hypertension found in early pregnancy. Design and method: We studied 74 pregnant patients referred for office hypertension found in the first trimester. Previous gestational or both gestational/preexisting hypertension was reported by 61 women, and previous miscarriage or stillbirth by 13 women. Mean patient age was 33.9 ± 4.7 years, and mean body mass index before pregnancy was 24.2 ± 3.3 kg/m 2 . ABPM was performed at 5, 10, 15, 20, 25, 30, 33, 35, and 37 weeks. To calculate overall antihypertensive treatment intensity per patient, we defined standard daily drug doses as labetalol 200 mg, methyldopa 750 mg, metoprolol 50 mg, nifedipine 20 mg, and verapamil 120 mg. Statistical analysis was performed using ANOVA. Results: All 75 children (73 single pregnancies and 1 twin pregnancy) were born alive (28 vaginal deliveries, 46 cesarean sections). Mean gestational age (current pregnancy) was 38.1 ± 2.1 (range 29–40) weeks, and mean birth weight was 3238 ± 561 (range 955–4200) g. Preeclampsia occurred in 10 women, and eclampsia in 3 women. The mean office blood pressure (BP) at the study entry (both treated and untreated patients) was 134.7/84.0 mmHg. ABPM showed normal BP values throughout the pregnancy in 5 patients who did not receive antihypertensive drugs. BP remained well controlled throughout the pregnancy (24-hour mean 120.7–126.8/74.6–78.1 mmHg). Most patients were treated with labetalol (n = 53 at 33–35 weeks, 100–600 mg/day) and methyldopa (n = 54 at 33 weeks, 500–2000 mg/day), with additional nifedipine (n = 10 at 37 weeks, 20–60 mg/day), verapamil (n = 8, 120–240 mg/day) and metoprolol (n = 1, 25–50 mg/day) as required. Treatment was generally initiated/intensified in response to mean ABPM values > 130/80 mmHg and/or maximum BP >160/100 mmHg. To maintain good BP control, the number of treated patients increased from 44 at 5 weeks to 63–65 at 25–35 weeks, and the average number of standard daily drug doses in treated patients increased from 1.65 at 5 weeks to 2.93 at 37 weeks (P < 0.001). Conclusions: Favorable pregnancy outcomes were obtained with serial ABPM-guided antihypertensive drug treatment for hypertension found during early pregnancy.